Relationship between Somatotype and Body Mass Index with the Successful Heading of Soccer Athletes - Amin, Syaiful (Sports Medicine Curiosity Journal, 2023)
The background of the problem is that there are many influencing factors, one of which is the compatibility of the body type somatotype and BMI that supports the sport involved. In order to get maximum performance, a condition is needed for players who have good physical abilities, techniques, and tactics and are supported by good somatotype conditions. This type of research is quantitative. One dependent variable is the heading ability of a soccer athlete, and two independent variables, namely somatotype and body mass index. The sample of this study were all football athletes from the Senopati club. Data research instruments used BMI measurement tests, anthropometry tests, and heading ability tests. The results of this study are that there is a good relationship between somatotype and the heading ability of soccer athletes, and there is a good relationship between body mass index and the heading ability of soccer athletes. The percentage is very good 50%, good 45%, and very bad 5%. The conclusion from the research results is that there is a good relationship between somatotype and the heading ability of soccer athletes, and there is a good relationship between body mass index and the heading abilities of soccer athletes.